Please answer this question.

Asked by Farheen1447 | 17th May, 2019, 06:38: AM

Expert Answer:

Q: 3:
Solution:
We have xy  = yx   
       →(2y)y = (y)2y      ......since x = 2y
       → 2yyy = yy+y  
       → 2yyy = yy yy
       → 2   = yy 
Taknig log on both the sides, we get
       → ylog2 = ylogy
       →   log2 = logy
       →       y = 2
x = 2y = 2 × 2 = 4 
→ x = 4 and y = 2.

 

Answered by Yasmeen Khan | 17th May, 2019, 10:02: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.